Evaluating the rail transport resource potential development level - L. Kalinichenko, L.; M. Chupyr, O.; V. Yanchenko, N.; M. Bredikhin, V.; O. Burlaka, Ye. (International Journal of Engineering and Technology, 2018)
The rail transport enterprises resource potential ensures the financial activity success, higher competitiveness and is the basis of economic growth. As the resource potential is dynamic, it needs to be managed. The effectiveness of such management needs a full and reliable evaluation of country's rail transport resource potential development level. The objective of the work is to study the approaches to evaluate the enterprises resource potential development level and to offer a proprietary technology on the basis of the final index for the rail transport enterprises of any country. The object of research is the resource potential of the rail transport enterprises. The methodological basis of the research is the fundamental provisions of management, the results of scientific research in the field of enterprises resource potential development to evaluate its level of development. The analysis of existing methods for evaluating the enterprises resource potential development level resulted into the technology for evaluating the level of development of the countryâ€™s rail transport enterprises resource potential by defining an integral index via hierarchy analysis method to determine the proportion of each component of the resource potential and to interpret the values of the integral index on the basis of Harrington verbal-numeric scale.Â Â Â